2022
DOI: 10.1063/5.0088062
|View full text |Cite
|
Sign up to set email alerts
|

Edge turbulence measurements in L-mode and I-mode at ASDEX Upgrade

Abstract: The I-mode confinement regime is promising for future reactor operation due to high energy confinement without high particle confinement. However, the role of edge turbulence in creating I-mode's beneficial transport properties is still unknown. New measurements of edge turbulence ([Formula: see text]) in L-modes and I-modes at low and high densities at ASDEX Upgrade are presented in this paper. A high radial resolution correlation electron cyclotron emission radiometer measures the broadband turbulence throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 43 publications
4
15
0
Order By: Relevance
“…The CECE channel and reflectometer are separated by approximately 4 mm. This corresponds to a poloidal velocity of approximately 3 km/s, which is similar to previously reported values at the L-mode and Imode WCM location [8]. This estimation is performed in the laboratory frame, and the background plasma velocity would be needed to calculate the WCM's phase velocity in the plasma frame.…”
Section: Wcm Lfeosupporting
confidence: 82%
See 1 more Smart Citation
“…The CECE channel and reflectometer are separated by approximately 4 mm. This corresponds to a poloidal velocity of approximately 3 km/s, which is similar to previously reported values at the L-mode and Imode WCM location [8]. This estimation is performed in the laboratory frame, and the background plasma velocity would be needed to calculate the WCM's phase velocity in the plasma frame.…”
Section: Wcm Lfeosupporting
confidence: 82%
“…the Quasi-Coherent Mode in Enhanced D-alpha Hmode and the Edge Harmonic Oscillation in Quiescent Hmode [6,7]). The WCM has been observed in the density and electron temperature fluctuation signals of AUG Lmodes as well [5,8]. A Low Frequency Edge Oscillation (LFEO) is also observed as a coherent and low-frequency mode in the pedestal of I-modes, and may be a Geodesic Acoustic Mode (GAM) [9].…”
Section: Introductionmentioning
confidence: 99%
“…CECE diagnostic provides a powerful technique for overcoming the noise limitations of stand ECE in measuring small amplitude temperature fluctuations. Recently CECE dianostic has been used to measure the electron temperature fluctuation in the improved energy confinement mode (I-mode) discharge in Asdex-upgrade, and interesting phenomenon have been observed [14].…”
Section: Cece System Upgradementioning
confidence: 99%
“…These temperature fluctuations are among the key parameters driving the turbulent electrostatic electron heat flux in tokamak plasmas [4]. Since the original implementation of the CECE diagnostic on W7-AS [5], follow-on studies on devices around the world have reported on important, transport-relevant experimental trends in turbulent electron temperature fluctuations using CECE data (see, e.g., ref's [6][7][8][9]). Additionally, data from the CECE diagnostic has and continues to serve as a key component in the validation of advanced gyrokinetic and gyrofluid models of plasma turbulence [10][11].…”
Section: Introductionmentioning
confidence: 99%